The Difference in Average Cholesterol in the BMI Group of TB-DM Sufferers at Dr Soetomo General Academic Hospital Surabaya - Pramesty, Theresia Trishavena Yuanita; Wahyunitisari, Manik R.; Yudhawati, Resti; Setiabudi, Rebekah J. (South Eastern European Journal of Public Health, 2024)
Introduction: Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by high blood glucose levels and impaired metabolism of carbohydrates, fats, and proteins due to inadequate insulin function. Individuals with DM are more susceptible to tuberculosis (TB) infection due to decreased metabolic function and compromised immune responses, including macrophage activity. Cholesterol plays a crucial role in macrophage phagocytosis of Mycobacterium tuberculosis. Patients with active TB generally have lower cholesterol levels compared to healthy individuals. This study investigates the relationship between cholesterol levels and Body Mass Index (BMI) in patients with Type 2 DM and TB. Objectives: To analyze differences in total cholesterol levels among BMI groups of Type 2 DM patients with TB at Dr Soetomo General Academic Hospital Surabaya. Methods: A cross-sectional study design was employed, involving 83 patients diagnosed with Type 2 DM and TB between 2021 and 2022. Data on cholesterol levels, BMI, and demographic characteristics were obtained from medical records. Statistical analysis was conducted using ANOVA to assess differences in cholesterol levels across BMI groups. Results: Among the 83 patients, 54% were male, and 61% were aged between 46 and 65 years. Most patients had normal cholesterol levels (75.9%) and normal BMI (61%). The ANOVA test showed no statistically significant difference in total cholesterol levels among the BMI groups (p = 0.90, p > 0.05). Conclusions: There was no significant difference in total cholesterol levels among BMI groups in Type 2 DM patients with TB at Dr. Soetomo General Academic Hospital Surabaya during 2021–2022. These findings suggest that BMI does not significantly influence cholesterol levels in this patient population.